Air-permeable antibacterial layered composite fabric, preparation method and application on medical protective clothing
Patent Information
- Application Number
- CN202610985434.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-03
- Publication Date
- 2026-10-20
- Estimated Expiration
- 2046-07-03
AI Technical Summary
然而,纯PLA本身不具备抗菌活性,需要引入抗菌组分进行改性
[0028]1、本发明将透气、抗菌性能优良的抗菌纤维膜与疏水改性面料层压复合,构建外层拒水,内层抗菌的层状复合面料。外层的疏水改性面料提供防水抗污染能力,内层抗菌纤维膜提供高效的抗菌功能,二者协同提高了面料的防护效果。其中,在抗菌纤维膜的制备过程中,本发明利用磺胺嘧啶改性聚乳酸与醛基化纳米氧化锌发生席夫碱反应,将有机抗菌剂与无机抗菌剂通过席夫碱键相结合,不仅提高了无机抗菌剂在聚乳酸基体中的相容性和分散性,同时由于席夫碱键对抗菌性能的加成作用,制成的有机-无机复合型抗菌剂具有更好的抗菌效果。
Smart Images

Figure CN122501044B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of layered fabric technology, specifically to a breathable and antibacterial layered composite fabric, its preparation method, and its application in medical protective clothing. Background Technology
[0002] Layered composite fabrics have become a research hotspot in the field of functional textiles due to their ability to combine the performance advantages of different materials. Functional textiles include medical protective clothing, whose fabrics need to simultaneously provide good barrier properties, excellent breathability and moisture permeability, and comfortable wear while offering antibacterial protection.
[0003] Currently, most medical protective clothing composite fabrics on the market are made of materials such as polypropylene and polyethylene, which are produced into nonwoven fabrics through processes such as meltblowing, and then laminated. To impart antibacterial properties to the fabric, existing technologies mostly involve adding inorganic or organic antibacterial agents in the finishing process. However, inorganic antibacterial agents are prone to aggregation and uneven distribution, resulting in unstable antibacterial effects and a stiffer fabric feel; organic antibacterial agents, on the other hand, have problems such as poor wash resistance and easy leaching, causing environmental pollution. In addition, physical blending or surface coating methods result in weak bonding between the antibacterial agent and the matrix material, leading to gradual depletion during use and making it difficult to guarantee the durability of antibacterial properties.
[0004] Polylactic acid (PLA), as a biodegradable polymer material, possesses excellent biocompatibility and processability, and is widely used in the biomedical field. However, pure PLA itself does not possess antibacterial activity, requiring modification by introducing antibacterial components. Therefore, developing a layered composite fabric with long-lasting antibacterial effects and excellent breathability and moisture permeability by stably and efficiently loading antibacterial agents into a PLA matrix is of significant practical importance for improving the overall performance of medical protective clothing. Summary of the Invention
[0005] The purpose of this invention is to overcome the shortcomings of existing technologies and provide a breathable antibacterial layered composite fabric, its preparation method, and its application in medical protective clothing. By laminating a breathable and antibacterial antimicrobial fiber membrane with a hydrophobic modified fabric, a layered composite fabric with an outer water-repellent layer and an inner antibacterial layer is constructed. The outer hydrophobic modified fabric provides waterproof and stain-resistant capabilities, while the inner antibacterial fiber membrane provides highly efficient antibacterial function; the two work synergistically to improve the fabric's protective effect. Specifically, in the preparation of the antibacterial fiber membrane, this invention utilizes a Schiff base reaction between sulfadiazine-modified polylactic acid and aldehyde-based nano-zinc oxide, combining organic and inorganic antibacterial agents through Schiff base bonds. This not only improves the compatibility and dispersibility of the inorganic antibacterial agent in the polylactic acid matrix but also, due to the additive effect of the Schiff base bonds on antibacterial properties, results in an organic-inorganic composite antibacterial agent with better antibacterial effects.
[0006] To achieve the above objectives, the technical solution adopted by the present invention is as follows:
[0007] A method for preparing a breathable and antibacterial layered composite fabric includes the following steps:
[0008] Step (1): Disperse nano zinc oxide in toluene, add KH550, stir to react, after the reaction is complete, centrifuge, wash, dry to obtain aminated nano zinc oxide;
[0009] Aminated nano-zinc oxide was dispersed in water, glyoxylic acid was added, and the reaction continued. After the reaction was completed, the nano-zinc oxide was centrifuged, washed, and dried to obtain aldehyde-modified nano-zinc oxide.
[0010] Step (2): Mix 2-chloro-N-(2-hydroxyethyl)-acetamide and lactide, add stannous octoate, react, and after the reaction is complete, dissolve, precipitate, and dry to obtain polylactic acid with chlorine-terminated end groups;
[0011] Chlorine-terminated polylactic acid and dichloromethane were mixed, and an aqueous solution of sodium sulfadiazine was added. Simultaneously, tetrabutylammonium bromide was added and mixed thoroughly. After the reaction was completed, the aqueous layer was collected, precipitated, and dried to obtain sulfadiazine-modified polylactic acid.
[0012] Step (3): Mix sulfadiazine-modified polylactic acid and N,N-dimethylformamide, add aldehyde-modified nano zinc oxide, react, filter, wash, and dry to obtain the antibacterial agent;
[0013] Step (4): Mix and dissolve polylactic acid, chloroform, and N,N-dimethylformamide, add antibacterial agent and mix evenly to obtain spinning solution;
[0014] Aluminum foil is placed on a roller as a receiving screen. The spinning solution is electrospun using an electrospinning machine. After spinning, a fiber membrane is formed. The fiber membrane is peeled off, laid flat and dried to obtain an antibacterial fiber membrane.
[0015] Step (5): Apply hot melt adhesive to one side of the antibacterial fiber membrane, attach the adhesive-coated side of the antibacterial fiber membrane to one side of the hydrophobic modified fabric, and hot press to obtain a breathable antibacterial layered composite fabric.
[0016] Preferably, in step (1), the ratio of nano zinc oxide, toluene, and KH550 is 2g:160-300mL:0.4-1g; the reaction conditions are: stirring at 60-80℃ for 10-14h.
[0017] Preferably, in step (1), the ratio of aminated nano zinc oxide, water, and glyoxylic acid is 1g:80-120mL:0.10-0.15g; the reaction conditions are: continue the reaction at 30-50℃ for 5-7h.
[0018] Preferably, in step (2), when preparing polylactic acid with chlorine-containing end groups: the ratio of 2-chloro-N-(2-hydroxyethyl)-acetamide, lactide, and stannous octoate is 1g:100-110g:0.01-0.05g; the reaction conditions are: vacuum, raising the temperature from 60℃ to 130℃ at a heating rate of 10-25℃ / h, then raising the temperature from 130℃ to 160℃ at a heating rate of 20-30℃ / h, and then raising the temperature to 170℃ for 2-4h.
[0019] Preferably, in step (2), when preparing sulfadiazine-modified polylactic acid, the ratio of chlorine-terminated polylactic acid, dichloromethane, sodium sulfadiazine aqueous solution, and tetrabutylammonium bromide is 10g:80-120mL:80-100mL:0.05-0.15g, and the concentration of sodium sulfadiazine aqueous solution is 6.0-6.5wt%; the reaction conditions are: stirring at room temperature for 10-14h.
[0020] Preferably, in step (3), the ratio of sulfadiazine-modified polylactic acid, N,N-dimethylformamide, and aldehyde-modified nano zinc oxide is 0.5-1.0g:100mL:1-2g; the reaction conditions are: reaction at 60-70℃ for 3-4h.
[0021] Preferably, in step (4), the mass ratio of polylactic acid, antibacterial agent, chloroform, and N,N-dimethylformamide is 10-15:1-3:60-70:30-40; the mixing conditions are: stirring and mixing at 60-70℃ for 6-8 hours.
[0022] Preferably, in step (4), the parameters for electrospinning are: positive voltage 20-25KV, negative voltage 1.0-1.5KV, solution injection speed 0.05-0.10mm / min, needle-to-roll distance 15-20cm, receiving speed 120-150r / min, and spinning machine translation speed 400-500mm / min.
[0023] Preferably, in step (5), the hydrophobic modified fabric is prepared by the following steps: immersing the polyester fabric in a finishing solution for 5-7 minutes, with a bath ratio of 1:30-50, one dip and one roll, with a roll-off rate of 70-90%, and after the immersion and roll-off are completed, taking it out and baking it at 140-160℃ for 2-5 minutes to obtain the hydrophobic modified fabric; wherein, the finishing solution contains 30-60g / L of fluorine-free waterproofing agent.
[0024] Preferably, in step (5): the amount of adhesive applied using the dispensing method is 10-15 g / m. 2 The hot pressing conditions are: hot pressing for 0.5-1.0 MPa pressure and 70-100℃ temperature for 0.5-2 min.
[0025] Preferably, a breathable antibacterial layered composite fabric is prepared using the method described above.
[0026] Preferably, the application of a breathable and antibacterial layered composite fabric as described above in medical protective clothing.
[0027] Compared with the prior art, the beneficial effects of the present invention are as follows:
[0028] 1. This invention laminates an antibacterial fiber membrane with excellent breathability and antibacterial properties with a hydrophobic modified fabric to construct a layered composite fabric with a water-repellent outer layer and an antibacterial inner layer. The outer hydrophobic modified fabric provides waterproof and stain-resistant capabilities, while the inner antibacterial fiber membrane provides highly efficient antibacterial function; the two work synergistically to improve the fabric's protective effect. Specifically, in the preparation of the antibacterial fiber membrane, this invention utilizes a Schiff base reaction between sulfadiazine-modified polylactic acid and aldehyde-based nano-zinc oxide to combine organic and inorganic antibacterial agents through Schiff base bonds. This not only improves the compatibility and dispersibility of the inorganic antibacterial agent in the polylactic acid matrix, but also, due to the additive effect of the Schiff base bonds on antibacterial properties, the resulting organic-inorganic composite antibacterial agent exhibits better antibacterial effects.
[0029] 2. In this invention, 2-chloro-N-(2-hydroxyethyl)-acetamide is used as an initiator to initiate the ring-opening polymerization of lactide, preparing polylactic acid with active chlorine end groups. This polylactic acid is then reacted with sodium sulfadiazine via a phase transfer catalytic reaction to prepare sulfadiazine-modified polylactic acid. Further, it undergoes a Schiff base reaction with aldehyde-modified nano-zinc oxide to produce an organic-inorganic composite antibacterial agent. Because the sulfadiazine-modified polylactic acid contains polylactic acid segments, it has good compatibility with the polylactic acid matrix, thus further improving the compatibility between nano-zinc oxide and the polylactic acid matrix. Simultaneously, the composite process of sulfadiazine-modified polylactic acid and aldehyde-modified nano-zinc oxide generates Schiff base bonds with antibacterial properties, which not only bridges the organic and inorganic antibacterial agents through chemical bonds, improving the stability of the antibacterial material in the matrix, but also further enhances the antibacterial performance of the antibacterial agent.
[0030] 3. This invention introduces an antibacterial agent into polylactic acid and produces a fiber membrane through electrospinning. Due to the high specific surface area and interconnected pore structure of the fiber membrane, it has good air and moisture permeability, improving the thermal and moisture comfort of the fabric. At the same time, the antibacterial agent has good compatibility with the polylactic acid matrix, and the antibacterial components are not easily washed out of the fiber, giving the antibacterial fiber membrane long-lasting antibacterial properties. The antibacterial fiber membrane is then combined with polyester knitted fabric that has been waterproofed with a fluorine-free waterproofing agent to construct a functional composite fabric with a waterproof and stain-resistant outer layer and a breathable and antibacterial inner layer, which synergistically improves the protective effect of the fabric, thus making it suitable for use in medical protective clothing. Attached Figure Description
[0031] Figure 1 This is a schematic diagram of the structure of the breathable and antibacterial layered composite fabric prepared by the present invention; in the figure, 1 is the hydrophobic modified fabric and 2 is the antibacterial fiber membrane.
[0032] Figure 2 This is a bar chart showing the antibacterial rate of the breathable and antibacterial layered composite fabrics prepared in Examples 1-5 and Comparative Examples 1-2 of this invention;
[0033] Figure 3 These are analysis charts showing the air permeability and moisture permeability of the breathable and antibacterial layered composite fabrics prepared in Examples 1-5 and Comparative Examples 1-2 of this invention. Detailed Implementation
[0034] The present invention will be further illustrated below through specific embodiments. The following embodiments are specific implementations of the present invention, but the implementation of the present invention is not limited to the following embodiments. Any changes, modifications, substitutions, combinations, or simplifications made without departing from the spirit and principle of the present invention shall be considered equivalent substitutions and are included within the protection scope of the present invention.
[0035] Example 1
[0036] This embodiment discloses a method for preparing a breathable and antibacterial layered composite fabric, including the following steps:
[0037] Step (1): Disperse 2g of nano zinc oxide in 200mL of toluene, add 0.6g of KH550, stir and react at 70℃ for 12h. After the reaction is completed, centrifuge to collect the precipitate, wash with ethanol and water, and dry at 60℃ for 12h to obtain aminated nano zinc oxide.
[0038] Take 1g of the above-prepared aminated nano zinc oxide and disperse it in 100mL of water. Add 0.11g of glyoxylic acid and react at 40℃ for 6h. After the reaction is completed, centrifuge to collect the precipitate, wash it with water, and dry it at 60℃ for 12h to obtain aldehyde-modified nano zinc oxide.
[0039] Step (2): Mix 1g of 2-chloro-N-(2-hydroxyethyl)-acetamide and 105g of lactide, add 0.04g of stannous octoate, evacuate the vacuum, raise the temperature from 60℃ to 130℃ at a heating rate of 20℃ / h, then raise the temperature from 130℃ to 160℃ at a heating rate of 30℃ / h, and then raise the temperature to 170℃ for 3h. After the reaction is completed, add dichloromethane to dissolve, precipitate with methanol, take the precipitate, and dry it at 40℃ for 24h to obtain polylactic acid with chlorine-containing end groups.
[0040] 10g of chlorine-terminated polylactic acid was mixed with 100mL of dichloromethane, and 80mL of 6.3wt% sodium sulfadiazine aqueous solution was added. At the same time, 0.1g of tetrabutylammonium bromide was added and mixed evenly. The mixture was stirred and reacted at room temperature for 12h. After the reaction was completed, the aqueous layer was collected, methanol was added to precipitate the precipitate, and the precipitate was dried at 40℃ for 24h to obtain sulfadiazine-modified polylactic acid.
[0041] Step (3): Mix 0.5g of sulfadiazine-modified polylactic acid and 100mL of N,N-dimethylformamide, add 1g of aldehyde-modified nano zinc oxide, react at 70℃ for 3h, filter after reaction, wash with methanol, and dry at 40℃ for 12h to obtain antibacterial agent.
[0042] Step (4): Mix and dissolve polylactic acid, chloroform, and N,N-dimethylformamide, add antibacterial agent and mix evenly, stir and mix at 70°C for 6 hours to obtain spinning solution;
[0043] The mass ratio of polylactic acid, antibacterial agent, chloroform, and N,N-dimethylformamide is 10:1:70:30.
[0044] Aluminum foil is placed on a roller as a receiving screen. The spinning solution is electrospun using an electrospinning machine. After spinning, a fiber membrane is formed. The fiber membrane is peeled off, laid flat and dried to obtain an antibacterial fiber membrane.
[0045] The parameters for electrospinning are as follows: positive voltage 25KV, negative voltage 1.5KV, solution injection speed 0.07mm / min, needle-to-roll distance 18cm, receiving speed 140r / min, and spinning machine translation speed 400mm / min.
[0046] Step (5): Apply hot melt adhesive to one side of the antibacterial fiber membrane using the dispensing method, with an adhesive application amount of 14 g / m². 2 The coated side of the antibacterial fiber membrane is bonded to one side of the hydrophobic modified fabric, and then hot-pressed at 0.5MPa pressure and 80℃ temperature for 1 minute to obtain a breathable antibacterial layered composite fabric.
[0047] The hydrophobic modified fabric is prepared by the following steps: immersing polyester fabric in a finishing solution for 6 minutes at a liquor ratio of 1:30, performing one dip and one roll, with a roll-off rate of 80%, removing the fabric after the dip and roll is completed, and baking it at 150℃ for 3 minutes to obtain the hydrophobic modified fabric; wherein the finishing solution contains 50g / L of fluorine-free waterproofing agent.
[0048] Example 2
[0049] This embodiment discloses a method for preparing a breathable and antibacterial layered composite fabric, including the following steps:
[0050] Step (1): Disperse 2g of nano zinc oxide in 200mL of toluene, add 0.6g of KH550, stir and react at 70℃ for 12h. After the reaction is completed, centrifuge to collect the precipitate, wash with ethanol and water, and dry at 60℃ for 12h to obtain aminated nano zinc oxide.
[0051] Take 1g of the above-prepared aminated nano zinc oxide and disperse it in 100mL of water. Add 0.11g of glyoxylic acid and react at 40℃ for 6h. After the reaction is completed, centrifuge to collect the precipitate, wash it with water, and dry it at 60℃ for 12h to obtain aldehyde-modified nano zinc oxide.
[0052] Step (2): Mix 1g of 2-chloro-N-(2-hydroxyethyl)-acetamide and 105g of lactide, add 0.04g of stannous octoate, evacuate the vacuum, raise the temperature from 60℃ to 130℃ at a heating rate of 20℃ / h, then raise the temperature from 130℃ to 160℃ at a heating rate of 30℃ / h, and then raise the temperature to 170℃ for 3h. After the reaction is completed, add dichloromethane to dissolve, precipitate with methanol, take the precipitate, and dry it at 40℃ for 24h to obtain polylactic acid with chlorine-containing end groups.
[0053] 10g of chlorine-terminated polylactic acid was mixed with 100mL of dichloromethane, and 80mL of 6.3wt% sodium sulfadiazine aqueous solution was added. At the same time, 0.1g of tetrabutylammonium bromide was added and mixed evenly. The mixture was stirred and reacted at room temperature for 12h. After the reaction was completed, the aqueous layer was collected, methanol was added to precipitate the precipitate, and the precipitate was dried at 40℃ for 24h to obtain sulfadiazine-modified polylactic acid.
[0054] Step (3): Mix 0.5g of sulfadiazine-modified polylactic acid and 100mL of N,N-dimethylformamide, add 1g of aldehyde-modified nano zinc oxide, react at 70℃ for 3h, filter after reaction, wash with methanol, and dry at 40℃ for 12h to obtain antibacterial agent.
[0055] Step (4): Mix and dissolve polylactic acid, chloroform, and N,N-dimethylformamide, add antibacterial agent and mix evenly, stir and mix at 70°C for 6 hours to obtain spinning solution;
[0056] The mass ratio of polylactic acid, antibacterial agent, chloroform, and N,N-dimethylformamide is 12:1.5:70:30.
[0057] Aluminum foil is placed on a roller as a receiving screen. The spinning solution is electrospun using an electrospinning machine. After spinning, a fiber membrane is formed. The fiber membrane is peeled off, laid flat and dried to obtain an antibacterial fiber membrane.
[0058] The parameters for electrospinning are as follows: positive voltage 25KV, negative voltage 1.5KV, solution injection speed 0.07mm / min, needle-to-roll distance 18cm, receiving speed 140r / min, and spinning machine translation speed 400mm / min.
[0059] Step (5): Apply hot melt adhesive to one side of the antibacterial fiber membrane using the dispensing method, with an adhesive application amount of 14 g / m². 2 The coated side of the antibacterial fiber membrane is bonded to one side of the hydrophobic modified fabric, and then hot-pressed at 0.5MPa pressure and 80℃ temperature for 1 minute to obtain a breathable antibacterial layered composite fabric.
[0060] The hydrophobic modified fabric is prepared by the following steps: immersing polyester fabric in a finishing solution for 6 minutes at a liquor ratio of 1:30, performing one dip and one roll, with a roll-off rate of 80%, removing the fabric after the dip and roll is completed, and baking it at 150℃ for 3 minutes to obtain the hydrophobic modified fabric; wherein the finishing solution contains 50g / L of fluorine-free waterproofing agent.
[0061] Example 3
[0062] This embodiment discloses a method for preparing a breathable and antibacterial layered composite fabric, including the following steps:
[0063] Step (1): Disperse 2g of nano zinc oxide in 200mL of toluene, add 0.6g of KH550, stir and react at 70℃ for 12h. After the reaction is completed, centrifuge to collect the precipitate, wash with ethanol and water, and dry at 60℃ for 12h to obtain aminated nano zinc oxide.
[0064] Take 1g of the above-prepared aminated nano zinc oxide and disperse it in 100mL of water. Add 0.11g of glyoxylic acid and react at 40℃ for 6h. After the reaction is completed, centrifuge to collect the precipitate, wash it with water, and dry it at 60℃ for 12h to obtain aldehyde-modified nano zinc oxide.
[0065] Step (2): Mix 1g of 2-chloro-N-(2-hydroxyethyl)-acetamide and 105g of lactide, add 0.04g of stannous octoate, evacuate the vacuum, raise the temperature from 60℃ to 130℃ at a heating rate of 20℃ / h, then raise the temperature from 130℃ to 160℃ at a heating rate of 30℃ / h, and then raise the temperature to 170℃ for 3h. After the reaction is completed, add dichloromethane to dissolve, precipitate with methanol, take the precipitate, and dry it at 40℃ for 24h to obtain polylactic acid with chlorine-containing end groups.
[0066] 10g of chlorine-terminated polylactic acid was mixed with 100mL of dichloromethane, and 80mL of 6.3wt% sodium sulfadiazine aqueous solution was added. At the same time, 0.1g of tetrabutylammonium bromide was added and mixed evenly. The mixture was stirred and reacted at room temperature for 12h. After the reaction was completed, the aqueous layer was collected, methanol was added to precipitate the precipitate, and the precipitate was dried at 40℃ for 24h to obtain sulfadiazine-modified polylactic acid.
[0067] Step (3): Mix 0.5g of sulfadiazine-modified polylactic acid and 100mL of N,N-dimethylformamide, add 1g of aldehyde-modified nano zinc oxide, react at 70℃ for 3h, filter after reaction, wash with methanol, and dry at 40℃ for 12h to obtain antibacterial agent.
[0068] Step (4): Mix and dissolve polylactic acid, chloroform, and N,N-dimethylformamide, add antibacterial agent and mix evenly, stir and mix at 70°C for 6 hours to obtain spinning solution;
[0069] The mass ratio of polylactic acid, antibacterial agent, chloroform, and N,N-dimethylformamide is 12.5:2:70:30.
[0070] Aluminum foil is placed on a roller as a receiving screen. The spinning solution is electrospun using an electrospinning machine. After spinning, a fiber membrane is formed. The fiber membrane is peeled off, laid flat and dried to obtain an antibacterial fiber membrane.
[0071] The parameters for electrospinning are as follows: positive voltage 25KV, negative voltage 1.5KV, solution injection speed 0.07mm / min, needle-to-roll distance 18cm, receiving speed 140r / min, and spinning machine translation speed 400mm / min.
[0072] Step (5): Apply hot melt adhesive to one side of the antibacterial fiber membrane using the dispensing method, with an adhesive application amount of 14 g / m². 2 The coated side of the antibacterial fiber membrane is bonded to one side of the hydrophobic modified fabric, and then hot-pressed at 0.5MPa pressure and 80℃ temperature for 1 minute to obtain a breathable antibacterial layered composite fabric.
[0073] The hydrophobic modified fabric is prepared by the following steps: immersing polyester fabric in a finishing solution for 6 minutes at a liquor ratio of 1:30, performing one dip and one roll, with a roll-off rate of 80%, removing the fabric after the dip and roll is completed, and baking it at 150℃ for 3 minutes to obtain the hydrophobic modified fabric; wherein the finishing solution contains 50g / L of fluorine-free waterproofing agent.
[0074] Example 4
[0075] This embodiment discloses a method for preparing a breathable and antibacterial layered composite fabric, including the following steps:
[0076] Step (1): Disperse 2g of nano zinc oxide in 200mL of toluene, add 0.6g of KH550, stir and react at 70℃ for 12h. After the reaction is completed, centrifuge to collect the precipitate, wash with ethanol and water, and dry at 60℃ for 12h to obtain aminated nano zinc oxide.
[0077] Take 1g of the above-prepared aminated nano zinc oxide and disperse it in 100mL of water. Add 0.11g of glyoxylic acid and react at 40℃ for 6h. After the reaction is completed, centrifuge to collect the precipitate, wash it with water, and dry it at 60℃ for 12h to obtain aldehyde-modified nano zinc oxide.
[0078] Step (2): Mix 1g of 2-chloro-N-(2-hydroxyethyl)-acetamide and 105g of lactide, add 0.04g of stannous octoate, evacuate the vacuum, raise the temperature from 60℃ to 130℃ at a heating rate of 20℃ / h, then raise the temperature from 130℃ to 160℃ at a heating rate of 30℃ / h, and then raise the temperature to 170℃ for 3h. After the reaction is completed, add dichloromethane to dissolve, precipitate with methanol, take the precipitate, and dry it at 40℃ for 24h to obtain polylactic acid with chlorine-containing end groups.
[0079] 10g of chlorine-terminated polylactic acid was mixed with 100mL of dichloromethane, and 80mL of 6.3wt% sodium sulfadiazine aqueous solution was added. At the same time, 0.1g of tetrabutylammonium bromide was added and mixed evenly. The mixture was stirred and reacted at room temperature for 12h. After the reaction was completed, the aqueous layer was collected, methanol was added to precipitate the precipitate, and the precipitate was dried at 40℃ for 24h to obtain sulfadiazine-modified polylactic acid.
[0080] Step (3): Mix 0.5g of sulfadiazine-modified polylactic acid and 100mL of N,N-dimethylformamide, add 1g of aldehyde-modified nano zinc oxide, react at 70℃ for 3h, filter after reaction, wash with methanol, and dry at 40℃ for 12h to obtain antibacterial agent.
[0081] Step (4): Mix and dissolve polylactic acid, chloroform, and N,N-dimethylformamide, add antibacterial agent and mix evenly, stir and mix at 70°C for 6 hours to obtain spinning solution;
[0082] The mass ratio of polylactic acid, antibacterial agent, chloroform, and N,N-dimethylformamide is 14:2.5:70:30.
[0083] Aluminum foil is placed on a roller as a receiving screen. The spinning solution is electrospun using an electrospinning machine. After spinning, a fiber membrane is formed. The fiber membrane is peeled off, laid flat and dried to obtain an antibacterial fiber membrane.
[0084] The parameters for electrospinning are as follows: positive voltage 25KV, negative voltage 1.5KV, solution injection speed 0.07mm / min, needle-to-roll distance 18cm, receiving speed 140r / min, and spinning machine translation speed 400mm / min.
[0085] Step (5): Apply hot melt adhesive to one side of the antibacterial fiber membrane using the dispensing method, with an adhesive application amount of 14 g / m². 2 The coated side of the antibacterial fiber membrane is bonded to one side of the hydrophobic modified fabric, and then hot-pressed at 0.5MPa pressure and 80℃ temperature for 1 minute to obtain a breathable antibacterial layered composite fabric.
[0086] The hydrophobic modified fabric is prepared by the following steps: immersing polyester fabric in a finishing solution for 6 minutes at a liquor ratio of 1:30, performing one dip and one roll, with a roll-off rate of 80%, removing the fabric after the dip and roll is completed, and baking it at 150℃ for 3 minutes to obtain the hydrophobic modified fabric; wherein the finishing solution contains 50g / L of fluorine-free waterproofing agent.
[0087] Example 5
[0088] This embodiment discloses a method for preparing a breathable and antibacterial layered composite fabric, including the following steps:
[0089] Step (1): Disperse 2g of nano zinc oxide in 200mL of toluene, add 0.6g of KH550, stir and react at 70℃ for 12h. After the reaction is completed, centrifuge to collect the precipitate, wash with ethanol and water, and dry at 60℃ for 12h to obtain aminated nano zinc oxide.
[0090] Take 1g of the above-prepared aminated nano zinc oxide and disperse it in 100mL of water. Add 0.11g of glyoxylic acid and react at 40℃ for 6h. After the reaction is completed, centrifuge to collect the precipitate, wash it with water, and dry it at 60℃ for 12h to obtain aldehyde-modified nano zinc oxide.
[0091] Step (2): Mix 1g of 2-chloro-N-(2-hydroxyethyl)-acetamide and 105g of lactide, add 0.04g of stannous octoate, evacuate the vacuum, raise the temperature from 60℃ to 130℃ at a heating rate of 20℃ / h, then raise the temperature from 130℃ to 160℃ at a heating rate of 30℃ / h, and then raise the temperature to 170℃ for 3h. After the reaction is completed, add dichloromethane to dissolve, precipitate with methanol, take the precipitate, and dry it at 40℃ for 24h to obtain polylactic acid with chlorine-containing end groups.
[0092] 10g of chlorine-terminated polylactic acid was mixed with 100mL of dichloromethane, and 80mL of 6.3wt% sodium sulfadiazine aqueous solution was added. At the same time, 0.1g of tetrabutylammonium bromide was added and mixed evenly. The mixture was stirred and reacted at room temperature for 12h. After the reaction was completed, the aqueous layer was collected, methanol was added to precipitate the precipitate, and the precipitate was dried at 40℃ for 24h to obtain sulfadiazine-modified polylactic acid.
[0093] Step (3): Mix 0.5g of sulfadiazine-modified polylactic acid and 100mL of N,N-dimethylformamide, add 1g of aldehyde-modified nano zinc oxide, react at 70℃ for 3h, filter after reaction, wash with methanol, and dry at 40℃ for 12h to obtain antibacterial agent.
[0094] Step (4): Mix and dissolve polylactic acid, chloroform, and N,N-dimethylformamide, add antibacterial agent and mix evenly, stir and mix at 70°C for 6 hours to obtain spinning solution;
[0095] The mass ratio of polylactic acid, antibacterial agent, chloroform, and N,N-dimethylformamide is 15:3:70:30.
[0096] Aluminum foil is placed on a roller as a receiving screen. The spinning solution is electrospun using an electrospinning machine. After spinning, a fiber membrane is formed. The fiber membrane is peeled off, laid flat and dried to obtain an antibacterial fiber membrane.
[0097] The parameters for electrospinning are as follows: positive voltage 25KV, negative voltage 1.5KV, solution injection speed 0.07mm / min, needle-to-roll distance 18cm, receiving speed 140r / min, and spinning machine translation speed 400mm / min.
[0098] Step (5): Apply hot melt adhesive to one side of the antibacterial fiber membrane using the dispensing method, with an adhesive application amount of 14 g / m². 2 The coated side of the antibacterial fiber membrane is bonded to one side of the hydrophobic modified fabric, and then hot-pressed at 0.5MPa pressure and 80℃ temperature for 1 minute to obtain a breathable antibacterial layered composite fabric.
[0099] The hydrophobic modified fabric is prepared by the following steps: immersing polyester fabric in a finishing solution for 6 minutes at a liquor ratio of 1:30, performing one dip and one roll, with a roll-off rate of 80%, removing the fabric after the dip and roll is completed, and baking it at 150℃ for 3 minutes to obtain the hydrophobic modified fabric; wherein the finishing solution contains 50g / L of fluorine-free waterproofing agent.
[0100] Comparative Example 1
[0101] This embodiment discloses a method for preparing a breathable and antibacterial layered composite fabric, including the following steps:
[0102] Step (1): Mix and dissolve polylactic acid, chloroform, and N,N-dimethylformamide, add nano zinc oxide and mix evenly, stir and mix at 70°C for 6 hours to obtain spinning solution;
[0103] The mass ratio of polylactic acid, nano zinc oxide, chloroform, and N,N-dimethylformamide is 10:1:70:30.
[0104] Aluminum foil is placed on a roller as a receiving screen. The spinning solution is electrospun using an electrospinning machine. After spinning, a fiber membrane is formed. The fiber membrane is peeled off, laid flat and dried to obtain an antibacterial fiber membrane.
[0105] The parameters for electrospinning are as follows: positive voltage 25KV, negative voltage 1.5KV, solution injection speed 0.07mm / min, needle-to-roll distance 18cm, receiving speed 140r / min, and spinning machine translation speed 400mm / min.
[0106] Step (2): Apply hot melt adhesive to one side of the antibacterial fiber membrane using the dispensing method, with an adhesive application amount of 14 g / m. 2 The coated side of the antibacterial fiber membrane is bonded to one side of the hydrophobic modified fabric, and then hot-pressed at 0.5MPa pressure and 80℃ temperature for 1 minute to obtain a breathable antibacterial layered composite fabric.
[0107] The hydrophobic modified fabric is prepared by the following steps: immersing polyester fabric in a finishing solution for 6 minutes at a liquor ratio of 1:30, performing one dip and one roll, with a roll-off rate of 80%, removing the fabric after the dip and roll is completed, and baking it at 150℃ for 3 minutes to obtain the hydrophobic modified fabric; wherein the finishing solution contains 50g / L of fluorine-free waterproofing agent.
[0108] Comparative Example 2
[0109] This embodiment discloses a method for preparing a breathable and antibacterial layered composite fabric, including the following steps:
[0110] Step (1): Mix 1g of 2-chloro-N-(2-hydroxyethyl)-acetamide and 105g of lactide, add 0.04g of stannous octoate, vacuum, raise the temperature from 60℃ to 130℃ at a heating rate of 20℃ / h, then raise the temperature from 130℃ to 160℃ at a heating rate of 30℃ / h, and then raise the temperature to 170℃ for 3h. After the reaction is completed, add dichloromethane to dissolve, precipitate with methanol, take the precipitate, and dry it at 40℃ for 24h to obtain polylactic acid with chlorine-containing end groups.
[0111] 10g of chlorine-terminated polylactic acid was mixed with 100mL of dichloromethane, and 80mL of 6.3wt% sodium sulfadiazine aqueous solution was added. At the same time, 0.1g of tetrabutylammonium bromide was added and mixed evenly. The mixture was stirred and reacted at room temperature for 12h. After the reaction was completed, the aqueous layer was collected, methanol was added to precipitate the precipitate, and the precipitate was dried at 40℃ for 24h to obtain sulfadiazine-modified polylactic acid.
[0112] Step (3): Mix 0.5g of sulfadiazine-modified polylactic acid with 1g of aldehyde-modified nano zinc oxide to obtain an antibacterial agent;
[0113] Step (4): Mix and dissolve polylactic acid, chloroform, and N,N-dimethylformamide, add antibacterial agent and mix evenly, stir and mix at 70°C for 6 hours to obtain spinning solution;
[0114] The mass ratio of polylactic acid, antibacterial agent, chloroform, and N,N-dimethylformamide is 10:1:70:30.
[0115] Aluminum foil is placed on a roller as a receiving screen. The spinning solution is electrospun using an electrospinning machine. After spinning, a fiber membrane is formed. The fiber membrane is peeled off, laid flat and dried to obtain an antibacterial fiber membrane.
[0116] The parameters for electrospinning are as follows: positive voltage 25KV, negative voltage 1.5KV, solution injection speed 0.07mm / min, needle-to-roll distance 18cm, receiving speed 140r / min, and spinning machine translation speed 400mm / min.
[0117] Step (5): Apply hot melt adhesive to one side of the antibacterial fiber membrane using the dispensing method, with an adhesive application amount of 14 g / m². 2 The coated side of the antibacterial fiber membrane is bonded to one side of the hydrophobic modified fabric, and then hot-pressed at 0.5MPa pressure and 80℃ temperature for 1 minute to obtain a breathable antibacterial layered composite fabric.
[0118] The hydrophobic modified fabric is prepared by the following steps: immersing polyester fabric in a finishing solution for 6 minutes at a liquor ratio of 1:30, performing one dip and one roll, with a roll-off rate of 80%, removing the fabric after the dip and roll is completed, and baking it at 150℃ for 3 minutes to obtain the hydrophobic modified fabric; wherein the finishing solution contains 50g / L of fluorine-free waterproofing agent.
[0119] In the above examples and comparative examples, the particle size of nano zinc oxide is 50-100 nm; KH550 is γ-aminopropyltriethoxysilane; the average molecular weight of polylactic acid is 150,000; the fluorine-free waterproofing agent is fluorine-free waterproofing agent R3; the hot melt adhesive is commercially available textile polyurethane hot melt adhesive; the polyester fabric is polyester knitted fabric with a weight of 140 g / m². 2 .
[0120] Test case
[0121] The performance of the breathable and antibacterial layered composite fabrics prepared in Examples 1-5 and Comparative Examples 1-2 was tested, and the specific test results are shown in Table 1:
[0122] Table 1
[0123]
[0124] The tests for each indicator in Table 1 were conducted according to the following standards: the antibacterial rate was determined by referring to GB / T 20944.3-2008 "Evaluation of antibacterial properties of textiles - Part 3: Vibration method", which was used to measure the antibacterial fiber membrane in the breathable antibacterial layered composite fabric; the moisture permeability was determined by referring to GB / T 12704.1-2009 "Test method for moisture permeability of textiles - Part 1: Moisture absorption method"; the air permeability was determined by referring to GB / T 5453-1997 "Determination of air permeability of textiles"; and the water contact angle was measured on the hydrophobic modified side of the breathable antibacterial layered composite fabric using a contact angle measuring instrument.
[0125] As can be seen from the test results in Table 1, the antibacterial fiber membrane prepared by the present invention has excellent antibacterial properties. When combined with hydrophobic modified fabric, it forms a layered composite fabric with good air permeability and moisture permeability, and also has waterproof properties.
[0126] In Comparative Example 1, the nano zinc oxide was not surface modified and no sulfadiazine-modified polylactic acid was added. Due to the high surface energy of the nano zinc oxide and the lack of functional groups that interact with the polylactic acid matrix, it is prone to agglomeration in the spinning solution and has poor dispersion in the fiber. At the same time, the lack of organic antibacterial agent sulfadiazine-modified polylactic acid and Schiff base bonds affects the antibacterial properties of the fiber membrane.
[0127] In Comparative Example 2, an antibacterial agent was prepared by mixing nano-zinc oxide and sulfadiazine-modified polylactic acid. Although both sulfadiazine-modified polylactic acid and nano-zinc oxide were used as antibacterial components, they were only physically mixed without forming chemical bonds through a Schiff base reaction. This resulted in the antibacterial agent exhibiting a phase-separated state within the fiber. On the one hand, the antibacterial effect provided by the Schiff base bond itself was lacking; on the other hand, the dispersion of nano-zinc oxide in the polylactic acid matrix was poor. Therefore, while the antibacterial performance of Comparative Example 2 was better than that of Comparative Example 1, it was still inferior to that of the Example.
[0128] It should be noted that the embodiments described above are only for explaining the present invention and do not constitute any limitation on the present invention. The present invention has been described with reference to typical embodiments, but it should be understood that the words used therein are descriptive and explanatory terms, not limiting terms. Modifications can be made to the present invention within the scope of the claims, and revisions can be made to the present invention without departing from the scope and spirit of the present invention. Although the present invention described herein relates to specific methods, materials, and embodiments, it does not mean that the present invention is limited to the specific examples disclosed herein; on the contrary, the present invention can be extended to all other methods and applications with the same function.
Claims
1. A method for preparing a breathable and antibacterial layered composite fabric, characterized in that, Includes the following steps: Step (1): Mix 2-chloro-N-(2-hydroxyethyl)-acetamide and lactide, add stannous octoate, react, and purify to obtain polylactic acid with chlorine-terminated end groups; Chlorine-terminated polylactic acid and dichloromethane were mixed, and then an aqueous solution of sodium sulfadiazine was added. Simultaneously, tetrabutylammonium bromide was added and mixed thoroughly. The mixture was reacted and purified to obtain sulfadiazine-modified polylactic acid. Step (2): Mix sulfadiazine-modified polylactic acid and N,N-dimethylformamide, add aldehyde-modified nano zinc oxide, react, purify, and obtain an antibacterial agent; The aldehyde-based nano zinc oxide is prepared by the following steps: Nano zinc oxide was dispersed in toluene, KH550 was added, the mixture was stirred and reacted, and after the reaction was completed, the mixture was centrifuged, washed and dried to obtain aminated nano zinc oxide. Aminated nano-zinc oxide was dispersed in water, glyoxylic acid was added, and the reaction continued. After the reaction was completed, the nano-zinc oxide was centrifuged, washed, and dried to obtain aldehyde-modified nano-zinc oxide. Step (3): Mix and dissolve polylactic acid, chloroform, and N,N-dimethylformamide, add antibacterial agent and mix evenly to obtain spinning solution. After electrospinning, dry the fiber membrane to obtain antibacterial fiber membrane. Step (4): The antibacterial fiber membrane is hot-pressed with the hydrophobic modified fabric to obtain a breathable antibacterial layered composite fabric.
2. The method for preparing a breathable and antibacterial layered composite fabric according to claim 1, characterized in that, In step (1), when preparing polylactic acid with chlorine-containing end groups: the ratio of 2-chloro-N-(2-hydroxyethyl)-acetamide, lactide, and stannous octoate is 1g:100-110g:0.01-0.05g; the reaction conditions are: vacuum, raising the temperature from 60℃ to 130℃ at a heating rate of 10-25℃ / h, then raising the temperature from 130℃ to 160℃ at a heating rate of 20-30℃ / h, and then raising the temperature to 170℃ for 2-4h.
3. The method for preparing a breathable and antibacterial layered composite fabric according to claim 1, characterized in that, In step (1), when preparing sulfadiazine-modified polylactic acid, the ratio of chlorine-terminated polylactic acid, dichloromethane, sodium sulfadiazine aqueous solution, and tetrabutylammonium bromide is 10g:80-120mL:80-100mL:0.05-0.15g, and the concentration of sodium sulfadiazine aqueous solution is 6.0-6.5wt%; the reaction conditions are: stirring at room temperature for 10-14h.
4. The method for preparing a breathable and antibacterial layered composite fabric according to claim 1, characterized in that, In step (2), when preparing aldehyde-modified nano zinc oxide: The ratio of nano zinc oxide, toluene, and KH550 is 2g:160-300mL:0.4-1g; the reaction conditions are: stirring at 60-80℃ for 10-14h. The ratio of aminated nano zinc oxide, water, and glyoxylic acid is 1g:80-120mL:0.1-0.15g; the reaction is continued at 30-50℃ for 5-7 hours.
5. The method for preparing a breathable and antibacterial layered composite fabric according to claim 1, characterized in that, In step (2), the ratio of sulfadiazine-modified polylactic acid, N,N-dimethylformamide, and aldehyde-modified nano zinc oxide is 0.5-1.0g:100mL:1-2g; the reaction conditions are: reaction at 60-70℃ for 3-4h.
6. The method for preparing a breathable and antibacterial layered composite fabric according to claim 1, characterized in that, In step (3): the mass ratio of polylactic acid, antibacterial agent, chloroform, and N,N-dimethylformamide is 10-15:1-3:60-70:30-40; the mixing conditions are: stirring and mixing at 60-70℃ for 6-8 hours; the electrospinning parameters are: positive voltage 20-25KV, negative voltage 1.0-1.5KV, solution injection speed 0.05-0.10mm / min, needle-to-roll distance 15-20cm, receiving speed 120-150r / min, and spinning machine translation speed 400-500mm / min.
7. The method for preparing a breathable and antibacterial layered composite fabric according to claim 1, characterized in that, In step (4), the hydrophobic modified fabric is prepared by the following steps: immersing the polyester fabric in the finishing solution for 5-7 minutes, with a bath ratio of 1:30-50, one dip and one roll, with a roll-off rate of 70-90%, and taking it out after the dip and roll is completed, and baking it at 140-160℃ for 2-5 minutes to obtain the hydrophobic modified fabric; wherein, the finishing solution contains 30-60g / L of fluorine-free waterproofing agent.
8. A breathable and antibacterial layered composite fabric prepared by the method of preparing the breathable and antibacterial layered composite fabric as described in any one of claims 1-7.
9. The application of the breathable and antibacterial layered composite fabric as described in claim 8 in medical protective clothing.
Citation Information
Patent Citations
Antibacterial polylactic acid fiber as well as preparation method and application thereof
CN121407253A
Antibacterial anti-mite hydrophobic polylactic acid fiber fabric and preparation method thereof
CN121756711A